Two New Species of Bibloplectus Reitter (Coleoptera: Staphylinidae: Pselaphinae) from the Orlando Park Collection, Field Museum of Natural History - Owens, Brittany E.; Carlton, Christopher E. (Zootaxa, 2018)
Two new species of Bibloplectus Reitter, 1881 are described from the Orlando Park Collection of Pselaphinae at the FMNH (Field Museum of Natural History, Chicago, IL, USA): Bibloplectus silvestris Owens and Carlton, new species (type locality, Urbana, IL, USA) and Bibloplectus wingi Owens and Carlton, new species (type locality, Shades State Park, IN, USA). Types of these new species were part of a series of specimens bearing unpublished Park manuscript names in both the pinned and slide collection at the FMNH. They bring the total number of species in the genus in eastern North America to twenty-three. Resolving these manuscript names adds to previous efforts to uncover elements of the hidden diversity of North American Bibloplectus from museum collections (Owens and Carlton 2016, Owens and Carlton 2017) and highlights the importance of close examination of the Orlando Park pselaphine collection as a valuable historic and taxonomic resource.